Perancangan Sistem Penerimaan Siswa Baru Berbasis Web Pada Sekolah Dasar Islam Plus Baitul Maal - Herfandi Herfandi; Saruni Dwiasnati; Kiki Ahmad Baihaqi; reza Avrizal (Faktor Exacta, 2022)
Islamic-based education in Indonesia is an educational institution that focuses on forming the character and knowledge of Islamic religious values. Islamic Elementary School Education Institute Plus Baitul Maal in carrying out educational administration procedures still uses the conventional system. The procedure that took place has not been efficient because prospective students are required to complete the registration form sheet by manual means and still stored in the folder. The implementation of information system technology in the education sector is able to provide convenience, especially in terms of efficientness, accuracy and novelty of information. Therefore, the design and creation of a website-based new student admission information system is expected to be able to solve the problem. This research resulted in a website-based new student admission information system with the main Page having Home, About Us, How to Apply, and Contact functionality. The student dashboard page has Home, Student Profile, Document functionality. The admin dashboard page has the functionality of Home, Website Content, Management, Document Completeness, and Settings as an admin user management serves to set up admin accounts (Create, Record, Update and Delete (CRUD) for admin accounts), development methods using waterfalls, research methods using qualitative and information system testing using black box testing that gets conclusions according to various functionality tests. This system is expected to ease the work of new student admission administrators as well as adjustments to education in the Industrial 4.0 era.